2011
DOI: 10.1002/stem.584
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Stem Cell-Secreted Vascular Endothelial Growth Factor Effects Poststroke Recovery, Inflammation, and Vascular Repair

Abstract: Cell transplantation offers a novel therapeutic strategy for stroke; however, how transplanted cells function in vivo is poorly understood. We show for the first time that after sub-acute transplantation into the ischemic brain of human central nervous system stem cells grown as neurospheres (hCNS-SCns), the stem cell-secreted factor, human VEGF (hVEGF), is necessary for cell-induced functional recovery. We correlate this functional recovery to hVEGF-induced effects on the host brain including multiple facets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
201
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(216 citation statements)
references
References 56 publications
(73 reference statements)
13
201
2
Order By: Relevance
“…Both numbers of eaten (A) and retrieved pellets (B) are higher in the cell group as compared to the vehicle group, the performance in the stroke-damaged animals receiving cell grafts being similar to that in the shamoperated group. In contrast, cell grafts did not improve performance It has been reported that human fetal NSCs through secretion of VEGF can improve behavioral performance already at 1 week after implantation and 2 weeks after stroke [11]. We found VEGF expression in the stroke-affected hemisphere of both lt-NES cell-transplanted and vehicle-injected animals, but the VEGF-immunoreactive areas were larger in animals implanted with lt-NES cells.…”
Section: Human Ipsc-derived Lt-nes Cells Induce Increased Vascular Encontrasting
confidence: 65%
See 2 more Smart Citations
“…Both numbers of eaten (A) and retrieved pellets (B) are higher in the cell group as compared to the vehicle group, the performance in the stroke-damaged animals receiving cell grafts being similar to that in the shamoperated group. In contrast, cell grafts did not improve performance It has been reported that human fetal NSCs through secretion of VEGF can improve behavioral performance already at 1 week after implantation and 2 weeks after stroke [11]. We found VEGF expression in the stroke-affected hemisphere of both lt-NES cell-transplanted and vehicle-injected animals, but the VEGF-immunoreactive areas were larger in animals implanted with lt-NES cells.…”
Section: Human Ipsc-derived Lt-nes Cells Induce Increased Vascular Encontrasting
confidence: 65%
“…Our hypothesis that the increased levels of VEGF in the lt-NES cell-transplanted animals could have an important role in the improved functional recovery was triggered by the study of Horie and coworkers [11]. They transplanted a different type of cell (NSCs derived from human fetus) in Nude rats subjected to distal MCAO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data in Table 1 are in part summarized in (Chamberlain et al, 2008;Hall et al, 2006;Martino and Pluchino 2006;Pluchino et al, 2009b;Rojewski et al, 2008;Uccelli et al, 2008;Yuan et al, 2011). (Cusimano et al, 2012;Jaderstad et al, 2010) aracrine IDO-kynurenine MSCs (h) T cells, DCs T cell apoptosis, inhibition of antigen presentation (Lanz et al, 2010;Matysiak et al, 2008Matysiak et al, , 2011Meisel et al, 2004;Plumas et al, 2005 Bonnamain et al, 2012;Chabannes et al, 2007;Moll et al, 2011) Paracrine VEGF NPCs Microglia/macrophages Inhibition of microglial activation, proliferation and phagocytosis (Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine LIF NPCs Th17 cells Inhibition of Th17 cell differentiation (Cao et al, 2011;Horie et al, 2011;Kim et al, 2009a;Mosher et al, 2012) Paracrine Galectins MSCs/NPCs T cells Inhibition of T cell proliferation (Gieseke et al, 2010;Sioud 2011;Yamane et al, 2010Yamane et al, , 2011 Endocrine/Paracrine TSG-6 MSCs Macrophages Inhibition of macrophage activation, proliferation and phagocytosis (Fisher-Shoval et al, 2012;Lee et al, 2009;Roddy et al, 2011) EVs miR transfer MSCs/NPCs Multiple Post-transcriptional regulation (Bruno et al, 2009;Chen et al, 2010;…”
mentioning
confidence: 99%
“…For the subacute phase, MSC transplantation has been shown to abrogate the early secondary cell death responses associated with stroke, such as dampening the oxidative stress, inflammation, mitochondrial impairment, and apoptosis [60]. On the other hand, MSC treatment in the chronic phase has been demonstrated to trigger brain remodeling via angiogenesis, vasculogenesis, neurogenesis, and synaptogenesis [61]. The minimally invasive intravenous or intra-arterial delivery of stem cells has been the preferred choice for the subacute phase due to an already injured brain produced by the primary ischemic insult, combined with chemoattractants that can guide migration of MSCs from the periphery to the brain.…”
Section: Mscs Their Mechanism Of Action and Safety Profilementioning
confidence: 99%